Effects of Neuroanatomic Structural Distances on Pituitary Function After Stereotactic Radiosurgery: A Multicenter Study. Issue 5 (17th May 2023) - Ironside, Natasha; Chen, Ching-Jen; Xu, Zhiyuan; Schlesinger, David; Lee Vance, Mary; Hong, Gregory K.; Jane, John A.; Patel, Samir; Bindal, Shray K.; Niranjan, Ajay; Lunsford, L. Dade; Liscak, Roman; et al.
Abstract : BACKGROUND: Delayed hypopituitarism is the most common complication after stereotactic radiosurgery (SRS) for pituitary adenomas. OBJECTIVE: To investigate the relationship between neuroanatomic structure distances from the radiation target and anterior pituitary function preservation after SRS through multicenter study. METHODS: We retrospectively reviewed the International Radiosurgery Research Foundation database from January 2002 to December 2021 for adult patients undergoing SRS for pituitary adenomas with >6 months of follow-up. Distances between centers or edges of hypothalamic-pituitary axis structures and SRS target volumes were measured using MRI. The primary outcome was anterior pituitary function preservation. Predictors were analyzed using multivariable logistic regression and area under the receiver operating curve (AUROC) curve analyses. RESULTS: Four hundred eighty-seven patients were categorized by preservation (n = 384) and no preservation (n = 103) of anterior pituitary function. The mean margin dose was 19.1(6.2) Gy. Larger distance from the center of the stalk to the tumor margin isodose was a positive predictor (adjusted odds ratio [aOR] = 1.162 [1.046-1.291], P = .005), while pre-SRS hypopituitarism (aOR = 0.646 [0.405-1.031], P = .067) and larger treatment volume (aOR = 0.965 [0.929-1.002], P = .061) were near negative predictors of the primary outcome. An interaction between the treatment volume and center stalk to margin isodose distance was found (aOR = 0.980 [0.961-0.999], P = .045). Center stalk to margin isodose distance had an AUROC of 0.620 (0.557-0.693), at 3.95-mm distance. For patients with treatment volumes of <2.34 mL, center stalk to margin isodose distance had an AUROC of 0.719 (0.614-0.823), at 2.95-mm distance. CONCLUSION: Achieving a distance between the center of the pituitary stalk and the tumor margin isodose ≥3.95 mm predicted anterior pituitary function preservation. For smaller treatment volumes <2.34 mL, the optimal distance was ≥2.95 mm. This may be modifiable during trans-sphenoidal resection to preserve pituitary function.